LITHIUM AND BORON OF SPRING WATER AND SALT CRUST FROM SALAR DE ASCOTÁN, SOUTHWESTERN ALTIPLANO - Valeria Hermosilla; Irma Vila; Sylvia V. Copaja (Journal of the Chilean Chemical Society, 2019)
Lithium is an essential element for humans and animals, it is bio accumulated by plants and it is a relatively uncommon element in the Earth ́s crust, on the contrary boron is widely distributed and it is micronutrient for plants. Boron and lithium are incorporated in fertilizers for agriculture and they used in many industries. Economically lithium is considered a strategic element because it is important in energy markets. There are two main economically recoverable sources of lithium, those being mineral ores and the evaporate deposits (playa lakes, called “salars” in Spanish). Direct extraction of lithium from brines at the salars is a low cost method and generates byproducts such as boron. Salars with high concentrations of Li have been reported in the Andean region near the borders of Chile, Bolivia, and Argentina. In Chile, the brines at Salar de Atacama are considered an important commercial source of lithium. To the northeast of Salar de Atacama it is located Salar de Ascotán (21º27`01, 9``S; 68º15`8,5``W) where the commercial boron extraction has been done for many decades but lacks published information about lithium extraction. In this study concentrations and distribution of lithium and boron in the water, sediment and salt crust were analyzed in some of the east-side springs which have a high endemic biodiversity. The concentrations in the salt crust were higher than in water and sediment. Geographically, the concentration of lithium in salt crust increases from north to south, but the boron concentration was higher in the extreme north and south, in the southernmost spring, Nº11. The average concentration of B in the salt crust was 149 [mg/Kg] and for Li was 3000 [mg/Kg] at the east side of the salar, thus it is the area with the highest concentration of lithium and boron. The concentrations in the salt crust were high and geographically heterogeneous for using a non-invasive method, for environmental protection we propose an exploration superficial on the western side which lack spring water and present the higher concentration of lithium and boron of the salar.